Empresa productora y comercializadora de puertas en madera en la ciudad de Armenia (Quindío) (2012)
This project is aimed at determining the feasibility that is within the department of Quindío, specifically in the city of Armenia, the conduct of a business including production and manufacturing of wooden doors on the market and that it creates the conditions necessary to stay within the association.